How to extend the realism today? - Juan Fernando Sellés (Civilizar, 2010)
This work investigates what is the philosophical realism. It offers a synthesis of what has been the realistic philosophy up to today regarding his discovery of the diverse senses of the act: Pure act, act of being created, intellect agent, cognitive innate and acquired habits, immanent cognitive operations, virtues of the will, acts of wanting. After that, it he proposes who it is possible to progress nowadays in the realism: discovering other senses of the act.